Maternal knowledge of obstetric danger signs and related factors among antenatal care attendees in Hargeisa, Somaliland: A cross-sectional analysis - Abdeta Muktar Ahmed; Mohamed Abdilahi Ahmed; Abdulkadir Mohammed Nuh; Hamse Khalif Hassan (PLoS ONE, 2026)
Background Maternal mortality remains a major global health challenge, disproportionately affecting low- and middle-income countries. Despite international efforts, nearly 95% of maternal deaths occur in these regions, with Sub-Saharan Africa bearing the highest burden. Limited knowledge of obstetric danger signs is a key factor contributing to delays in seeking care, which in turn increases the risk of preventable maternal complications. Evidence on maternal awareness in Somaliland is scarce. Objective This study aimed to assess the level of knowledge of obstetric danger signs and associated factors among pregnant women attending antenatal care in Hargeisa, Somaliland. Methods A facility-based cross-sectional study was conducted from July 2 to August 4, 2022, among pregnant women attending antenatal care services. A total of 222 participants were selected using a systematic random sampling technique from eight maternal and child health centers. Data were collected through face-to-face interviews using a pretested and structured questionnaire and analyzed with SPSS version 25. Bivariate and multivariate logistic regression was carried out. Results About 35.6% had a good knowledge specifically about pregnancy related obstetric danger signs. Only 57 women (25.7%) demonstrated overall good knowledge of obstetric danger signs across pregnancy, childbirth, and the postpartum periods. Knowledge was highest for vaginal bleeding (65% − 67%), while less visible complications such as convulsions and blurred vision were less frequently mentioned. Multivariate analysis revealed that secondary level education or higher (AOR = 3.6, 95% CI: 1.8–7.3), access to and usage of media (AOR = 2.6, 95% CI: 1.2–5.6), and institutional delivery (AOR = 3.4, 95% CI: 1.6–7.2), were significant predictors of knowledge. Conclusion Maternal knowledge of obstetric danger signs in Hargeisa was low. Targeted health education, broader use of mass media, and promoting institutional delivery are critical strategies to improve and reduce preventable maternal mortality.